Anchoring and variations in the social representations of corruption [Ancoragens e variações nas representações sociais da corrupção] - Gabrielle Poeschl (2010)
In this paper, we examine the representations of corruption of Portuguese respondents and attempt to identify variations according to different social groups and to the general, global, or national contexts in which the phenomenon is considered. We found that